2012
DOI: 10.1007/s00411-011-0399-0
|View full text |Cite
|
Sign up to set email alerts
|

Boron delivery with liposomes for boron neutron capture therapy (BNCT): biodistribution studies in an experimental model of oral cancer demonstrating therapeutic potential

Abstract: Boron neutron capture therapy (BNCT) combines selective accumulation of (10)B carriers in tumor tissue with subsequent neutron irradiation. We previously demonstrated the therapeutic efficacy of BNCT in the hamster cheek pouch oral cancer model. Optimization of BNCT depends largely on improving boron targeting to tumor cells. Seeking to maximize the potential of BNCT for the treatment for head and neck cancer, the aim of the present study was to perform boron biodistribution studies in the oral cancer model em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…No systemic toxicity or side effects have been observed in any biodistribution studies performed with the use of TAC and MAC (35). It is also noteworthy that both compounds are readily attainable by straightforward, high-yield, scalable processes, and they are stable for long periods of time before administration.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…No systemic toxicity or side effects have been observed in any biodistribution studies performed with the use of TAC and MAC (35). It is also noteworthy that both compounds are readily attainable by straightforward, high-yield, scalable processes, and they are stable for long periods of time before administration.…”
mentioning
confidence: 98%
“…Research efforts by our group and affiliates (35) are currently directed at applying the treatment protocol reported here to other cancer types and have, in some instances, achieved complete cancer remission. Furthermore, ongoing neutron dose-escalation studies performed on the same cancer type (EMT6) by using our delivery system have demonstrated enhanced tumor control beyond the results presented in this report.…”
mentioning
confidence: 99%
“…Our previous biodistribution studies with this model using MAC-TAC liposomes showed that tumor boron values peaked at 67 ppm after 48 h with a very favorable 10:1 tumor/ normal tissue ratio (30). Thus, this protocol was very attractive for radiobiological study.…”
mentioning
confidence: 85%
“…SI Materials and Methods provides detailed experimental procedures. Also, please refer to our previously published boron biodistribution study (30) for a detailed description of MAC-TAC liposome administration protocols.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation